Comparison of mesenchymal stem cells from bone marrow and adipose tissue for bone regeneration in a critical size defect of the sheep tibia and the influence of platelet-rich plasma - Niemeyer, Philipp; Fechner, Katharina; Milz, Stefan; Richter, Wiltrud; Suedkamp, Norbert P.; Mehlhorn, Alexander T.; Pearce, Simon; Kasten, Philip (Biomaterials, 2010)
Aim of the present study was to compare the osteogenic potential of bone marrow derived mesenchymal stem cells (BMSC) and adipose-tissue derived stem cells (ASC) and to evaluate the influence of platelet-rich plasma (PRP) on the osteogenic capacity of ASC in a large animal model. Ovine BMSC (BMSC-group) and ASC (ASC-group) were seeded on mineralized collagen sponges and implanted into a critical size defect of the sheep tibia (n=5 each). In an additional group, platelet-rich plasma (PRP) was used in combination with ASC (PRP-group). Unloaded mineralized collagen (EMPTY-group) served as control (n=5 each). Radiographic evaluation was performed every 2 weeks, after 26 weeks histological analysis was performed. Radiographic evaluation revealed a significantly higher amount of newly formed bone in the BMSC-group compared to the ASC-group at week 10 and compared to EMPTY-group from week 12 (all p<0.05). A superiority on radiographic level concerning bone formation of the PRP-group versus the empty control group was found (p<0.05), but not for the ASC-group. Histological analysis confirmed radiographic evaluation finding analogous significances. In conclusion, ASC seem to be inferior to BMSC in terms of their osteogenic potential but that can partially be compensated by the addition of PRP.